Pengaruh Pemberian Topikal ASI terhadap Pelepasan Tali Pusat di BPM Anatapura dan BPM Setia: Influence of Breastfeeding Giving Topical to Old Release of Umbilical Cord - Dwi Yani Ratna Dewi; Muliani; Tondong, Henrietta Imelda (Jurnal Bidan Cerdas, 2018)
The background of cord care is to keep the umbilical cord clean, dry and help protect newborns from possible infections. The umbilical cord fades faster and reduces the risk of infection. The content of breast milk, namely leukocyte cells, proteolytic enzymes, and immunological substances that can help accelerate the release of the umbilical cord. The study aimed to determine the effect of topical breastfeeding on the length of umbilical cord release in newborns at BPM Anatapura and Setia Palu BPM. The method used was pre-experiment with Static Group Comparison. The study population was all newborns aged 0 days until the cord was released, born at BPM Anatapura and BPM Setia Palu. The sample was divided into 2 groups (intervention and control), the number of samples was 15 for each group, so that a total of 30 samples were taken by consecutive sampling technique. Data analysis used was univariate and bivariate with Independent t-test. The results showed that the mean cord release in the topical breastfeeding group (102.7+ 22.08 hours) was smaller than the open dry treatment group (145, 36+ 37.63 hours) in the 95% CI with Ï-value of 0.001. The topical ASI group had a chance of 1.42 times (42.66 hours) experiencing umbilical cord release more quickly than the open dry treatment group. The conclusion of the study was the effect of topical breastfeeding on the length of umbilical cord release. The results of the study can be used as reference references in providing health services, especially simple umbilical cord care using topical breast milk.